2018
DOI: 10.1063/1.5012878
|View full text |Cite
|
Sign up to set email alerts
|

Structure formation and surface chemistry of ionic liquids on model electrode surfaces—Model studies for the electrode | electrolyte interface in Li-ion batteries

Abstract: Ionic liquids (ILs) are considered as attractive electrolyte solvents in modern battery concepts such as Li-ion batteries. Here we present a comprehensive review of the results of previous model studies on the interaction of the battery relevant IL 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([BMP]+[TFSI]−) with a series of structurally and chemically well-defined model electrode surfaces, which are increasingly complex and relevant for battery applications [Ag(111), Au(111), Cu(111), prist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 86 publications
(133 reference statements)
15
45
1
Order By: Relevance
“…On lithiated HOPG, this was explained by the complete desorption of EC at low temperatures (≈200 K), where the mobility of Li + in the bulk of lithiated HOPG is too low to segregate toward the surface and react with the adsorbate phase . We recently demonstrated that Li can in fact easily deintercalate from the bulk of lithiated HOPG, but only at temperatures higher than 230 K and only in the presence of a strongly adsorbed species such as an ionic liquid adlayer (desorption temperature >400 K), which chemically stabilizes the surface Li …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On lithiated HOPG, this was explained by the complete desorption of EC at low temperatures (≈200 K), where the mobility of Li + in the bulk of lithiated HOPG is too low to segregate toward the surface and react with the adsorbate phase . We recently demonstrated that Li can in fact easily deintercalate from the bulk of lithiated HOPG, but only at temperatures higher than 230 K and only in the presence of a strongly adsorbed species such as an ionic liquid adlayer (desorption temperature >400 K), which chemically stabilizes the surface Li …”
Section: Resultsmentioning
confidence: 99%
“…One possible way to determine the initial stages of the SEI formation at the EEI at the atomic/molecular level involves the use of surface science techniques, studying the interaction of individual components of electrolytes, such as the typical key component EC (or other electrolyte components like ionic liquids), with well‐defined model electrodes under idealized ultrahigh‐vacuum (UHV) conditions, which is focus of the ongoing work in our laboratory. Following a previous study on the interaction of EC with Li‐free and lithiated highly oriented pyrolytic graphite (HOPG) as model for the anode, we here report the results of a similar type of study on the interaction of EC with well‐defined LiCoO 2 electrode surfaces, both fully oxidized LiCoO 2 and partly reduced LiCoO 2− δ surfaces, as models for the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…A highly oriented pyrolytic graphite test substrate cooled to 80 K (no intercalation) was used for calibration of the Li deposition rate. [14] Deposition rates in MLE of approximately 0.04-0.05 MLE min À 1 were calculated from the damping of the C 1s substrate) peak after successive vapor deposition of Li at temperatures where Li adsorbs on the surface. For the evaluation we assume that 1 MLE of Li has a thickness d of 2.48 Å, equivalent to the (110) interplanar distance in a body centered cubic lattice (the most stable configuration of a Li metal at r.t.).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in our model approach, we reduced the complexity significantly, and prepare well-defined model electrodes like Co 3 O 4 (111) thin film electrodes, under idealized ultrahigh vacuum (UHV) conditions, and explore the interaction of individual components of the battery electrolyte (e. g., ionic liquids, carbonates, lithium) using surface science techniques. [11][12][13][14][15][16][17][18] In particular ionic liquids (ILs), [19][20][21][22] that are organic salts with a melting point below 100°C, got into the focus as promising solvents in battery electrolytes, [23][24] as they are, for example, not flammable, such reducing the hazard of battery fires. [25] Consequently, they represent an important class of compounds whose interactions with electrodes need to be studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation